Methane Activation on Pt2+ Sites on Pt/TiO2 with Adsorbed Nitrate Species as Evidenced by In Situ FTIR Spectroscopy - Murakami, Junichi; Vargheese, Vibin; Bando, Kyoko K. (Journal of physical chemistry. C, 2022)
Identification of methane (CH4) activation sites on solid catalysts in CH4 oxidation is crucial to provide understanding for the conversion of CH4 to valuable oxygenates and thus has been a subject of intensive research. It has been suggested in many experimental and theoretical studies that oxidized metal sites, i.e., cationic sites, are responsible for CH4 activation. However, clear spectroscopic evidence for this has been lacking. Here, we show that CH4 is activated on the cationic sites, which was demonstrated by examining the oxidation processes of CH4 to CO with nitrates (NO3 –) on a titania-supported platinum (Pt/TiO2) sample. The reaction was analyzed by in situ Fourier transform infrared (FTIR) spectroscopy and in situ X-ray absorption near edge structure (XANES) measurement. It was found that upon the formation of NO3 – on the sample, cationic sites (Pt2+) form and CH4 was converted to CO on Pt2+ at 220 °C and then on metallic sites (Pt0) at 270 °C. The switch of the CO formation sites is attributed to the conversion of Pt2+ to Pt0 during the oxidation reaction. The results indicate that Pt2+ is the site for CH4 activation.